Analysis of the Difficulty Level of the Final Semester Exam Questions for Electrical Power Installation Subject - Riswanti, Indah; Candra, Oriza (Universitas Negeri Padang, 2021)
This study aims to determine the quality of the Final Semester Examination questions for even the Electrical Power Installation subject class XI of the Electrical Power Installation Engineering skill program at SMK Negeri 5 Padang for the 2020/2021 academic year in terms of the level of difficulty in multiple choice questions. The research method used in this study is a quantitative descriptive method with documentary data collection techniques which were analyzed using the SPSS Version 25 program. The subjects in this study were class XI TITL students at SMK Negeri 5 Padang in the 2020/2021 school year. Based on the results of the analysis, it shows that of the 30 multiple choice questions with the level of difficulty, the questions that are classified as difficult are 1 item (3%), the questions that are classified as moderate are 12 items (40%), and the questions that are classified as easy are 17 items (57%). Questions can be followed up with questions that are categorized as moderate and can be stored in the question bank to be reused in the next test. Questions that are categorized as easy and difficult can be corrected or revised before being used again. So it can be concluded that the level of difficulty of the questions is included in the questions of passably.Â